Membrane and method for manufacturing the same

JP2025026929AInactive Publication Date: 2025-02-26G20 WATER TECH LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024200252
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-21
Filing Date
2024-11-18
Publication Date
2025-02-26
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025026929000001
    Figure 2025026929000001
Patent Text Reader

Abstract

To provide more advanced membranes having properties including improved and tuneable fouling resistance, size exclusion, higher selectivity, higher productivity at lower energy inputs, longer life span, improved chemical and mechanical resistance and fewer manufacturing defects.SOLUTION: There is described a separation membrane, suitably for water separation. The membrane comprises a porous substrate layer and an active layer arranged over at least a part of the substrate layer. The active layer comprises a lamellar structure comprising at least two layers of treated two-dimensional material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to separation membranes. More specifically, the present invention relates to post-coating processing of membranes containing two-dimensional materials and to the production of membranes having different coating layers of two-dimensional materials. [Background technology]

[0002] Membrane separation involves the use of porous materials to separate mixtures of components and is typically performed with or without a driving force, such as pressure, applied to the membrane surface, e.g., by gravity.

[0003] Membrane separation may be applied to liquid-liquid, solid-liquid, ion-liquid, liquid-gas, and gas-gas separations.

[0004] Membrane separation is favored in principle because of its low cost, small installation space, low heat input, low energy consumption, low chemical processing, high removal efficiency, and low need for regeneration of spent media compared to other water treatment or separation technologies. Membrane separation is widely applicable in water treatment for the removal of solids, particulates, organic molecules, dissolved species, ions, microorganisms, dye molecules, bacteria, natural organic matter, milk concentration, and viruses. Membrane separation is used in many applications ranging from industrial wastewater treatment, domestic water purification, food and beverage processing, dairy processing, laundry water treatment, landfill leachate, paper and pulp wastewater, fine chemical manufacturing, oily water treatment to seawater desalination.

[0005] Separation membranes are usually classified according to their characteristic pore size and intended application. Microfiltration membranes (MF) have pore sizes ranging from 0.1 to 100 μm and can be used to remove bacteria, cysts, yeast cells, suspended particles, pigments, and asbestos. Ultrafiltration membranes (UF) have pore sizes ranging from 0.01 μm to 0.1 μm and can be used to remove proteins, colloidal particles, and viruses. Nanofiltration membranes (NF) have pore sizes ranging from 0.001 to 0.01 μm and can be used to select multivalent ions, dissolved compounds, medium-sized organic molecules, small proteins, small colloidal particles, etc. Reverse osmosis membranes (RO) have pore sizes less than 0.001 μm and can be used to remove ions and small organic molecules.

[0006] Currently, commercially available separation membranes perform adequately in a wide range of applications. However, to produce new clean water resources and protect existing water resources at lower capital and operating costs, more advanced membranes with properties such as improved and tunable fouling resistance, size exclusion, higher selectivity, higher productivity with low energy input, longer life, improved chemical and mechanical resistance, and fewer manufacturing defects are needed. Therefore, new materials, membrane systems, and processing technologies with properties that meet these demands are desirable. Summary of the Invention [Problem to be solved by the invention]

[0007] Nanoporous materials may be applied in water separation membranes, however, the use of such materials presents challenges related to scalability, mechanical strength, chemical robustness, lifetime, solubility in liquid media, and also challenges related to the high cost of materials and subsequent manufacturing processes required to incorporate nanoporous materials. Therefore, there is a need for improved membranes for separation, particularly water treatment applications. Therefore, it is an object of aspects of the present invention to address one or more of the above problems or other problems. [Means for solving the problem]

[0008] According to a first aspect of the present invention there is provided a separation membrane, preferably for water separation, comprising a porous substrate layer and an active layer disposed on at least a portion of the substrate layer, the active layer comprising a lamellar structure comprising at least two layers of processed two-dimensional material.

[0009] As used herein, "treated" in reference to a two-dimensional material means that the two-dimensional material has been subjected to a process after formation of a coating composition comprising the two-dimensional material and / or after application (application) of the two-dimensional material to a substrate layer, which has caused a change in the functional groups of the two-dimensional material, e.g., changed the number, type and / or distribution of functional groups, compared to the functional groups of the two-dimensional material before the treatment, preferably before application of the two-dimensional material to a substrate, preferably after application of the two-dimensional material to a substrate layer.

[0010] According to a second aspect of the present invention, there is provided a method for producing a separation membrane, preferably a membrane according to the first aspect of the present invention, comprising the steps of: a. optionally preparing a substrate, optionally by treating said substrate with a chemical treatment and / or a radiation treatment and / or a plasma treatment and / or a heat treatment; b. contacting the substrate with a composition comprising a two-dimensional material, optionally by forming a first layer of a composition comprising a two-dimensional material, and then applying (adding) a further layer of a composition comprising a two-dimensional material to the first layer, said layer optionally being allowed to dry before application of a subsequent layer; c. optionally drying the membrane; d. treating the two-dimensional material applied in step (b) such as by applying high energy radiation such as laser radiation, chemicals, high temperature, thermal energy and / or pressure to the two-dimensional material, optionally prior to application and subsequent treatment of further layers of said composition, to cause a change in the functional groups of said two-dimensional material by treating said first layer of said composition; e. Optionally, drying the membrane. A method is provided that includes:

[0011] According to a third aspect of the present invention there is provided a separation membrane, preferably for water separation, comprising a porous substrate layer and an active layer disposed on at least a portion of the substrate layer, the active layer comprising at least two coating layers each comprising a two-dimensional material, at least one of the coating layers of the active layer being different from another coating layer of the active layer.

[0012] It will be apparent that the phrase "at least one of the coating layers of the active layer is different from another coating layer of the active layer" refers to a substantial difference between the coating layers that results in a substantial difference in separation activity. It will also be apparent that "different" does not include one of the coating layers being disposed above the other coating layer.

[0013] The active layer of the membrane of the third aspect of the invention may comprise one or more further coating layers, each of which may be the same as another coating layer or may be different from the other coating layers.

[0014] A coating layer may include a different structure (e.g., due to the presence of nanochannels in the layer and / or a greater or lesser thickness) and / or a different composition than another coating layer. A coating layer may include two-dimensional materials with different functional groups, different amounts of functional groups, different structures (e.g., different particle / plate structures and / or sizes) than another layer. A coating layer may include additional additives and / or additional two-dimensional materials to another layer.

[0015] Suitably, the coating layer of the active layer may comprise a lamellar structure comprising a two-dimensional material.

[0016] According to a fourth aspect of the present invention, there is provided a method for producing a separation membrane, preferably a membrane according to the first or third aspect of the present invention, comprising the steps of: a. optionally preparing a substrate, optionally by treating said substrate with a chemical treatment and / or a radiation treatment and / or a plasma treatment and / or a heat treatment; b. contacting the substrate with a composition comprising a two-dimensional material to form a first coating layer; c. applying one or more further coating layers of one or more compositions comprising a two-dimensional material to the first layer, optionally drying one or more of said layers between the application of subsequent layers; d. Optionally, drying the membrane. wherein at least one of the plurality of coating layers is different from another coating layer.

[0017] In the method according to the fourth aspect of the invention, at least one of the coating compositions used to form the layers may be different from another of the coating compositions.

[0018] The active layer of the membrane of the present embodiment may comprise nanochannels, and preferably the coating composition for forming the active layer comprises nanofibers. The nanochannels may have a diameter or width of 1 to 100 nm. The method of the second embodiment may comprise the step of removing the nanofibers by contacting the membrane with a weak acid.

[0019] According to a fifth aspect of the present invention there is provided a membrane, preferably a membrane according to any aspect of the present invention, wherein the active layer comprises nanochannels having a diameter in the range of 1 to 100 nm.

[0020] According to a sixth aspect of the present invention, there is provided a method for producing a separation membrane, preferably a membrane according to any aspect of the present invention, comprising the steps of: a. optionally providing a substrate; b. contacting the substrate with a coating composition comprising a two-dimensional material and nanofibers; c. removing said nanofibers by contacting the membrane produced by step (b) with a weak acid, for example an acid having a pH between 1 and 6; d. treating, preferably reducing, said two-dimensional material, preferably by laser treatment, chemical treatment and / or heat treatment; e. optionally drying the membrane. A method is provided that includes:

[0021] The membranes of the invention may be for any kind of separation, such as liquid separation, liquid / gas separation, gas / gas separation, liquid / solid separation, etc. Preferably, the membranes of the invention are for oil / water separation, molecular separation, pharmaceutical separation for removing pharmaceutical residues in aquatic environments, drug separation, biofiltration, e.g. separation of microorganisms and water, desalination, preferably seawater desalination, or selective ion separation, and nuclear wastewater separation for removing nuclear radioactive elements from nuclear wastewater, heavy metal removal, biorefinery, laundry water treatment, milk concentration, blood treatment, such as physiological separation and blood separation for replacing damaged kidney filters, and / or separation of bioplatform molecules from plant, e.g. grass, sources, or domestic water treatment, industrial water treatment, e.g. industrial laundry effluent, food and beverage production, chemical manufacturing effluent, paper processing, wastewater from landfills, agriculture, dairy and cheese production (including salt water treatment from cheese production), milk concentration, protein recovery from crops such as potatoes, etc. Preferably, the membranes are for oil / water separation and desalination.

[0022] The substrate layer of any of the aspects of the invention may comprise any porous material operable to support an active layer during a separation process. The substrate may comprise one or more layers of the same or different porous materials. The different porous materials may differ in chemical composition, thickness, morphology and / or structure.

[0023] The substrate may include polymeric substrates, polymeric substrates with inorganic fillers, ceramic substrates, composite substrates, metal substrates such as thin film composite substrates, inorganic substrates, inorganic-organic substrates, metal substrates, woven filaments such as woven monofilaments or woven multifilaments, and / or nonwoven substrates, and / or cast substrates. Woven filament and nonwoven substrates may be formed from fibers having the same or different chemical properties, for example, such substrates may include a first component formed from a first material and a second component formed from a second material, for example a mixture of polypropylene (PP) and polyethylene terephthalate (PET). Preferably, the substrate is a ceramic substrate or a polymeric substrate such as polysulfone or polyethersulfone, polyamide substrate, polyvinylidene fluoride (PVDF), or a zeolite or alumina substrate, most preferably a polymeric substrate.

[0024] The substrate may be in the form of a porous film, a porous plate, a porous hollow fiber substrate, a tubular fiber substrate, a bulk porous material, etc. Suitably, the substrate is in the form of a film, preferably a substantially planar film.

[0025] The porous film may be selected from ceramic porous films, polymeric porous films, polymeric nonwoven films, and inorganic-organic porous films, and is preferably a polymeric porous film or a polymeric nonwoven film.

[0026] The substrate may include at least two porous films, porous plates, porous fibrous substrates, and / or bulk porous materials.

[0027] Advantageously, substrates comprising multiple porous films, porous plates, porous fibrous substrates, and / or bulky porous materials can provide improved mechanical properties, improved flux, and / or reduced costs.

[0028] The ceramic porous substrate may be formed from a material selected from one or more of zeolite, silicon, silica, alumina, zirconia, mullite, bentonite, and montmorillonite clay substrates.

[0029] The polymeric porous woven or nonwoven substrate may be formed from a material selected from one or more of polyacrylonitrile (PAN), polyethylene terephthalate (PET), polycarbonate (PC), polyamide (PA), polysulfone (PSf), poly(ether)sulfone (PES), modified poly(ether)sulfone (m-PES), cellulose acetate (CA), poly(piperazine-amide), polyvinylidene fluoride (PVDF), polypropylene (PP), polytetrafluoroethylene (PTFE), poly(phthalazinone ether sulfone ketone) (PPESK), polyamide-urea, poly(ether ether ketone), polypropylene, poly(phthalazinone ether ketone), and thin film composite porous film (TFC). Suitably, the TFC comprises an ultra-thin "barrier" layer polymerised in situ on a porous polymeric support membrane, for example commercially available polyamide-derived TFCs of interfacially synthesised polyamides formed on polysulfone membranes, and / or other TFCs such as poly(piperazine-amide) / poly(vinyl alcohol) (PVA), polypiperazine amide / poly(phthalazinone biphenyl ether sulfone) (PPBES), hydrolysed cellulose triacetate (CTA) / cellulose acetate (CA) TFCs, chlorinated polyvinyl chloride (CPVC), polylactic acid (PLA), PET / PP or mixtures of different polymers, non-woven layers or composite layers, for example a support layer coated with a cast layer.

[0030] The polymer substrate for deposition may be selected from one or more of polyamide (PA), polysulfone (PSf), polyvinylidene fluoride (PVDF), polycarbonate (PC), cellulose acetate (CA), cellulose triacetate (TCA), polyethylene terephthalate (PET), poly(ether)sulfone (PES), modified poly(ether)sulfone (m-PES), polypropylene (PP), polyacrylonitrile (PAN), thin film composites (TFCs) such as polysulfone-supported polyamide composite substrates, chlorinated polyvinyl chloride (CPVC), polylactic acid (PVA), PET / PP.

[0031] The substrate may include a nonwoven substrate, or a composite substrate in which the substrate comprises a mixture of different polymers, such as a substrate including a support layer coated with a cast layer thereon.

[0032] Preferably, the polymer substrate is selected from one or more of polyamide (PA), polysulfone (PSf), polyvinylidene fluoride (PVDF), and thin film composite (TFC), such as a polysulfone-supported polyamide composite substrate.

[0033] The porous substrate may be a nanotechnology-based porous substrate, such as a nanostructured ceramic porous substrate, an inorganic-organic porous substrate, a nanoporous nonwoven fabric, and / or a nanoparticle-doped membrane.

[0034] The nanostructured ceramic porous substrate may be formed of two or more layers, preferably comprising a first layer including a conventional pressure-driven ceramic material such as one or more of zeolite, titanium oxide, alumina, zirconia, etc., and a second layer extending over at least a portion of the first layer, preferably the second layer being zeolite, titanium oxide, alumina synthesized via hydrothermal crystallization or dry gel conversion methods, etc. Other nanostructured ceramic porous substrates may be reactive substrates or catalyst-coated ceramic surface substrates. Such substrates may advantageously provide strong interactions with the active layer, improving the stability of the filter.

[0035] The inorganic-organic composite porous substrate may be formed from inorganic particles contained in a porous organic polymer substrate. The inorganic-organic composite porous substrate may be formed from a material selected from zirconia nanoparticles with polysulfone porous membrane. Advantageously, the inorganic-organic composite porous substrate may provide a combination of an easy-to-manufacture, low-cost substrate with good mechanical strength, and / or improved selectivity (e.g., improved oil separation). An inorganic-organic porous substrate such as zirconia nanoparticles with polysulfone may advantageously provide high permeability. Other inorganic-organic porous substrates may be selected from thin-film nanocomposite substrates containing one or more types of inorganic particles, metal-based foams (aluminum foam, copper foam, lead foam, zirconium foam, tin foam, gold foam, etc.), and mixed matrix substrates containing inorganic fillers in an organic matrix to form an organic-inorganic mixed matrix.

[0036] The porous substrate may comprise a nano-nonwoven. Advantageously, the nano-nonwoven provides high porosity, high surface area, and / or controllable functionality. The nonwoven may comprise nanoscale fibers in diameter. The nonwoven may be formed from cellulose acetate, cellulose, polyethylene terephthalate (PET), polyolefins such as polyethylene and polypropylene, and / or polyurethane, preferably by electrospinning, preferably using cellulose acetate and polyurethane.

[0037] The substrate may be manufactured as flat sheet material, plates, or hollow fibers and may be one of several types of membrane substrates such as hollow fiber substrates, tubular substrates, or spiral wound membrane substrates. Suitable flat sheet substrates may be obtained from Dow Filmtec or GE Osmonics.

[0038] Advantageously, a substrate in the form of a porous polymeric substrate can provide increased ease of processing and / or lower costs.

[0039] The substrate layer may have any suitable pore size. The average size of the pores in the substrate may be 0.1 nm to 30,000 nm, preferably 200 nm to 5000 nm, depending on the application. The substrate is typically a microfiltration membrane or an ultrafiltration membrane.

[0040] The pore size of the substrate layer may be 0.1 nm to 100,000 nm, for example 0.5 nm to 50,000 nm, 1 nm to 25,000 nm, 5 nm to 20,000 nm, 10 nm to 10,000 nm, for example 50 nm to 9,000 nm, 100 nm to 8,500 nm, 100 nm to 8,000 nm, 120 nm to 8,000 nm, 150 nm to 7,500 nm, for example 200 nm to 5,000 nm. Preferably, the pore size of the substrate is smaller than the particles of the two-dimensional material. For example, when graphene is in the form of particles with a size of 500 nm, the pore size of the porous substrate is preferably smaller than 500 nm.

[0041] The substrate may have any suitable thickness. The thickness of the substrate may be 0.1 to 20,000 μm, or 0.1 to 15,000 μm, for example, 0.5 to 10,000 μm, or 1 to 5,000 μm, or 3 to 2,500 μm, preferably 5 to 1,500 μm, more preferably 10 to 1,200 μm, for example, 15 to 1,000 μm, or 20 to 900 μm, for example, 25 to 800 μm. Optionally, the substrate may have a thickness of 5 to 700 μm, for example, 8 to 600 μm, or 8 to 500 μm, preferably 10 to 450 μm.

[0042] Preferably, the thickness of the substrate is 10 to 1,000 μm.

[0043] Preferably, the substrate is selected from a polysulfone substrate, a polyamide substrate and / or a ceramic substrate. The substrate may be selected from a polypropylene substrate, a polytetrafluoroethylene substrate and / or a ceramic substrate.

[0044] Preferably, the ceramic substrate is selected from one of zeolites, titanium oxide, and zirconia, for example, zeolites and zirconia.

[0045] The substrate may have a surface roughness, suitably Rz, of, for example, 0 to 1 μm, for example less than 500 nm or less than 300 nm, for example less than 200 nm or less than 100 nm, preferably less than 70 nm or less than 50 nm, more preferably less than 30 nm. Advantageously, a low surface roughness can provide improved uniformity of the structure of the active layer.

[0046] The surface of the substrate operable to receive the active layer may be hydrophilic. Suitably, the contact angle of the coating composition on the substrate surface is less than 90°, for example less than 70°, preferably less than 50°.

[0047] The substrate may be suitably treated, such as chemically, radiation, plasma and / or thermally, prior to application of the coating composition, preferably chemically and / or radiation. Suitably, the substrate is treated over a portion of the surface to be contacted with the coating composition.

[0048] Advantageously, treatment of the surface of the substrate can provide enhanced interfacial adhesion and uniformity of the coating layer, and therefore enhance the membrane's life and / or performance during water treatment, such as selectivity, rejection rate, transport rate (flux rate), and improved uniformity of the active layer.

[0049] For example, the surface of the substrate operable to receive the coating composition may have been subjected to hydrophilization. Advantageously, the hydrophilization of the surface may improve the wetting properties and the interfacial adhesion. The treatment of said substrate may include the addition, preferably the formation, of surface functional groups and / or the addition of hydrophilic additives. The surface functional groups introduced may include one or more of hydroxyl groups, ketone groups, aldehyde groups, carboxylic acid groups and amine groups. The formation of functional groups may be achieved by one of the following techniques: plasma treatment, redox reaction, radiation, UV-ozone treatment and / or chemical treatment. The hydrophilic additive may be selected from polyvinyl alcohol, polyethylene glycol, nanofillers, surface-modifying polymers and zwitterions. The addition of the hydrophilic additive may be performed by coating or depositing an additive having the desired functionality on the treated membrane surface.

[0050] Advantageously, the surface treatment of the polymer substrate can result in improved uniformity of the active layer on the substrate, for example by improving the fluidity and wettability of the surface by the coating material. The surface treatment can also improve the adhesion of the active layer on the substrate by improving the wettability of the surface by the coating liquid, which can further improve separation efficiency and lifespan. The presence of the above hydrophilicity and / or functionality on the polymer substrate provides an active layer with a more uniform structure, improved continuity, improved adhesion, and improved separation efficiency. The hydrophilicity and / or functionality can also provide the membrane with extended filter lifespan and stability.

[0051] Surface treatments can also improve properties, including membrane antifouling performance, enhanced salt rejection and / or enhanced molecular selectivity and / or enhanced permeability. Fouling leads to reduced membrane flux and service life. Fouling can be caused by one or more of the following: organic fouling, biofouling, particulate fouling, and colloidal fouling.

[0052] In the case of ceramic and metal substrates, it is preferred that the substrate not be treated.

[0053] A coating composition comprising the two-dimensional material, i.e., the two-dimensional material in at least partially pretreated form, may be deposited on a substrate to form an active layer.

[0054] The coating composition of any aspect of the present invention may include a two-dimensional material along with a carrier and / or a metal oxide.

[0055] The two-dimensional material may comprise one or more of graphene or its derivatives, silicene, germanene, stanene, boron nitride, preferably h-boron nitride, carbon nitride, metal-organic nanosheets, polymers, graphene aerogels, two-dimensional metal-organic frameworks, three-dimensional metal-organic frameworks, and / or transition metal dichalcogenides and their derivatives.

[0056] Preferably, said two-dimensional material comprises graphene or a derivative thereof.

[0057] Derivatives of graphene may include any graphene-based material such as graphene oxide, reduced graphene oxide from graphene oxide, reduced graphene oxide by bottom-up processes, oxidized graphene by processing from graphite, functionalized graphene, functionalized graphene oxide, functionalized reduced graphene oxide, and / or functionalized oxidized graphene, composites thereof, and dispersions thereof.

[0058] The above two-dimensional materials of the active layer may be prepared using any of the suitable methods known to those skilled in the art. Two-dimensional silicene, germanium and stanene may be prepared by surface-assisted epitaxial growth under ultra-high vacuum. Hexagonal two-dimensional h-boron nitride may be prepared by several methods, such as mechanical cutting, unzipping of boron nitride nanotubes, chemical functionalization and sonication, solid-state reactions, solvent exfoliation and sonication. Among these methods, chemical methods have been found to give the highest yields. For example, h-boron nitride may be synthesized on a single crystal transition metal substrate using borazine as the boron source and nitride source. Two-dimensional carbon nitride can be prepared by direct microwave heating of melamine and carbon fibers. Metal-organic frameworks (MOFs) can be prepared by in situ solvothermal synthesis by mixing the raw materials at high temperatures, such as 100-140°C, followed by separation. Two-dimensional molybdenum disulfide can be obtained by several methods, including mechanical exfoliation, liquid exfoliation, and chemical exfoliation. Among these methods, chemical exfoliation has been found to provide a high yield. One example is chemical exfoliation, where molybdenum disulfide is chemically exfoliated using lithium with centrifugation and separation. Two-dimensional tungsten disulfide can be prepared by deposition-thermal annealing method: tungsten is vacuumed or deposited, followed by adding sulfur and thermal annealing. Polymer / graphene aerogels can be produced by coupling polyethylene glycol-grafted graphene oxide followed by freeze-drying.

[0059] The graphene or its derivatives may include any graphene-based material such as graphene oxide, reduced graphene oxide, hydrated graphene, amino-based graphene, alkylamine-functionalized graphene oxide, ammonia-functionalized graphene oxide, amine-functionalized reduced graphene oxide, octadecylamine-functionalized reduced graphene oxide, hydrazide-functionalized graphene, hydrazine-functionalized graphene, amide-functionalized graphene, amine-PEG-functionalized graphene, graphene composites, and / or polymer graphene aerogels. Preferably, the graphene or its derivatives is graphene oxide. Graphene and its derivatives may be commercially available from Sigma-Aldrich and / or any other suitable manufacturers.

[0060] The two-dimensional material may be in the form of a single layer or multiple layers, preferably multiple layers. The two-dimensional material may be formed from particles comprising a single layer, two layers or multiple layers of the two-dimensional material, multiple being defined as 3 to 10 layers. Suitably, the particles of the two-dimensional material comprise 1 to 50 layers, for example 2 to 20 layers or 3 to 10 layers. Suitably, at least 30% by weight of the particles comprise 1 to 8 layers, for example 2 to 6 layers or 3 to 5 layers, more preferably at least 40%, 50%, 60%, 70%, most preferably at least 80%, or at least 90%, or 95%, or 98% or 99% by weight of such number of layers. The number of layers in a particle may be measured using atomic force microscopy (AFM or transmission electron microscopy (TEM)) (TT-AFM, AFM workshop Co., California, USA).

[0061] The d-spacing between adjacent lattice planes in the particles of the two-dimensional material may be from 0.34 nm to 1000 nm, such as from 0.34 nm to 500 nm, or from 0.4 to 500 nm, or from 0.4 to 250 nm, for example from 0.4 to 200 nm, or from 0.4 to 150 nm, or from 0.4 to 100 nm, or from 0.4 to 50 nm, or from 0.4 to 25 nm, or from 0.4 to 20 nm, or from 0.4 to 18 nm, for example from 0.45 to 17 nm, 0.45 to 16 nm, 0.45 to 15 nm, or from 0.45 to 14 nm, for example from 0.45 to 10 nm.

[0062] The size distribution of the two-dimensional material may be such that at least 30% by weight of the two-dimensional material has a lateral size of 1 nm to 20,000 nm, e.g., 2 to 15,000 nm, 5 nm to 10,000 nm, 10 nm to 7,500 nm, e.g., 15 nm to 3,500 nm, 20 nm to 3,000 nm, or 25 nm to 3,000 nm, suitably 30 nm to 2,500 nm, 40 nm to 2,500 nm, or preferably 50 nm to 2,500 nm, more preferably at least 40 wt%, 50 wt%, 60 wt%, 70 wt%, most preferably at least 80 wt%, or at least 90 wt%, or 95 wt%, or 98 wt%, or 99 wt%. The size and size distribution of GO may be measured using transmission electron microscopy (TEM, JEM-2100F, JEOL Ltd., Japan).

[0063] For example, the lateral size of the two-dimensional material may be measured using transmission electron microscopy (TEM, JEM-2100F, JEOL Ltd., Japan), and the number (Ni) of nanosheets (Mi) with the same size may be measured. Then, the average size may be calculated by Equation 1.

number

[0064] The oxygen atomic content of the two-dimensional material may be in the range of 1% to 60%, such as 2% to 50%, for example 3% to 45%, or 5% to 44%, or 10% to 44%, preferably 15% to 44%.

[0065] The two-dimensional material may be present in the coating composition in an amount of 0.0001% to 20% by weight, such as 0.0002% to 10% by weight, for example 0.001 to 5% by weight, preferably 0.005 to 1% by weight, such as 0.01% to 0.5% by weight, or 0.02% to 0.5% by weight, relative to the total weight of the composition (paste).

[0066] The carrier may be water, an organic solvent or a mixture thereof. Preferably, the carrier is selected from ethanol, propanol, glycol, tertiary butanol, acetone, dimethyl sulfoxide, a mixture of dimethyl sulfoxide / alcohol / glycol, a mixture of water / alcohol / glycol, a mixture of glycol / water / tertiary butanol, a mixture of water / acetone, a mixture of water / ethanol, N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide (DMSO), ethylene glycol (EG), N-methyl-2-pyrrolidone, isopropyl alcohol, mineral oil, dimethylformamide, terpineol, ethylene glycol, or a mixture thereof.

[0067] Preferably, the carrier is water / ethanol, such as 50 / 50% by volume water / ethanol, water optionally with one or more stabilizers, such as lithium oxide; N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, N,N-diethylformamide or terpineol, most preferably water:ethanol, such as 50:50% by volume water / ethanol, N,N-dimethylformamide, N,N-diethylformamide. Preferably, it is water.

[0068] The composition comprising the two-dimensional material having an oxygen atomic content of 30% or less may further comprise a surfactant, and preferably the composition comprises water as a carrier and a surfactant.

[0069] The coating composition may contain additives to tailor the properties of the active layer, such as other metals and / or fibers, e.g., metal oxide fibers in the form of nanostrands; and / or dopants such as Au, Fe, Cu, Cu(OH)2, Cd(OH)2, and / or Zr(OH)2. Such additives may be added to the membrane to control the pore size and channel structure of the two-dimensional material, forming micro- and nano-channels for high water transport rates.

[0070] Preferably, the composition includes fibers, preferably in the form of metal oxide nanostrands. Any type of suitable fiber may be used, such as continuous or stapled fibers. The metal oxide nanostrands may be selected from one or more of Cu(OH)2, Cd(OH)2, and Zr(OH)2.

[0071] The fibers used to form the nanochannels may have a diameter of 0.1 to 1000 nm, for example, 0.1 to 850 nm, 0.2 to 750 nm, 0.3 to 500 nm, or 0.4 to 250 nm, or 0.45 to 150 nm, or 0.45 to 100 nm, 0.45 to 75 nm, preferably 0.45 to 50 nm, or 0.45 to 10 nm, preferably 0.45 to 5 nm.

[0072] The length of the fibres may be in the range of 1 nm to 100 μm, for example 2 nm to 75 μm, or 3 nm to 50 μm, for example 100 nm to 15 μm, or 500 nm to 10 μm.

[0073] When the coating composition is to be applied by printing, the length of the fibers may be in the range of 2 nm to 10 μm, preferably 100 nm to 10 μm, more preferably 200 nm to 10 μm. If the length is too long, it may cause clogging of the nozzle, and if it is too short, it may only cause caving.

[0074] The fibers may be present in the coating composition at a concentration of 0.01% to 150% of the two-dimensional material concentration, such as 0.01% to 100%, 0.01% to 50%, 0.01% to 20%, preferably 0.01% to 10%.

[0075] The concentration of the fibers in the coating composition may be 0.0001 mg / ml to 10 mg / ml, for example, 0.0005 mg / ml to 9 mg / ml, 0.001 mg / ml to 8 mg / ml, for example, 0.005 mg / ml to 7 mg / ml, 0.007 mg / ml to 6 mg / ml, for example, 0.008 mg / ml to 5.5 mg / ml, 0.009 mg / ml to 5 mg / ml, for example, 0.01 mg / ml to 4.5 mg / ml, 0.02 mg / ml to 4 mg / ml, for example, 0.03 mg / ml to 3.5 mg / ml, 0.04 mg / ml to 3 mg / ml, for example, 0.05 mg / ml to 2.5 mg / ml.

[0076] Preferably, the fibers are removed prior to use, such as by mechanical removal or dissolution. For example, after the coating composition has been applied to the substrate, the fibers may be removed, for example, by dissolving with an acid, such as an acid having a pH of 1-6, preferably ethylenediaminetetraacetic acid, for example, by immersing the membrane in an acidic solution, such as 0.15 M EDTA in water, preferably for 20 minutes, optionally followed by repeated washing with deionized water. Advantageously, the use of fibers such as metal oxide nanostrands can significantly improve the water transport rate of the membrane while maintaining a similar salt / molecule rejection rate.

[0077] The coating composition of any embodiment of the present invention may be prepared by dispersing or dissolving one or more components in a carrier or solvent using one or a combination of mechanical mixing, such as leading edge-trailing blade stirring, ceramic ball grinding and milling, mechanical mixing using a Silverson high shear mixer, mechanical milling with glass beads, such as an Eiger Torrance mortar mill, an Ultra Turrax homogenizer, grinding with a mortar and pestle, mechanical roll milling, ultrasonic treatment, non-sonic treatment. The fibers may be mixed with the coating composition in a dispersed state by ultrasonic treatment or mechanical blending.

[0078] A centrifuge may be used to filter out agglomerates or large sized components in the coating composition.

[0079] Pre-separation of the coating composition may be used to control the size and size distribution of the components for a desired coating process, for example, the coating composition may be passed through a 0.45 μm polymer membrane to form an ink for an inkjet printer with a 20 μm nozzle size.

[0080] The method according to any of the aspects of the present invention may include coating the coating composition onto the substrate using gravity deposition, vacuum suction or suction or vapor deposition, dip coating, pressure deposition, printing, preferably digital printing, such as inkjet printing, aerosol printing, 3D printing, offset lithography printing, gravure printing, flexographic printing techniques, pad printing, bar coating, curtain coating, dip coating, spin coating, screen coating, gravure coating, and other printing or coating techniques known to those skilled in the art.

[0081] Preferably, the coating composition is coated onto the substrate using bar coating, flexographic coating, inkjet printing, screen coating or slot coating.

[0082] The inkjet printing method may be, for example, piezoelectric or thermal drop-on-demand (DOD) inkjet printing; or continuous inkjet printing (CIJ); preferably, the inkjet printing is DOD inkjet printing.

[0083] The drop volume of the cartridge may be 1 pl to 1000 pl, or 1 pl to 500 pl, or 2 pl to 250 pl, or 3 pl to 100 pl, preferably 5 to 50 pl, or 8 to 30 pl, for example 10 pl. The voltage and firing frequency of the inkjet printing method may depend on the waveform of the coating composition. The firing voltage may be 10 to 50 V. The firing frequency may be 3 kHz to 30 kHz, preferably about 5 kHz. The cartridge temperature of the inkjet printer may be 10°C to 50°C, preferably about 20°C to 40°C. The stage temperature of the inkjet printer may be 20°C to 60°C, preferably about 21°C.

[0084] The coating speed depends on the coating application method. For example, the coating speed for inkjet printing, flexographic printing or bar coating may be from 0.01 m / s to 500 m / s, such as from 0.03 m / s to 450 m / s, from 0.05 m / s to 400 m / s, from 0.08 m / s to 350 m / s, such as from 0.1 m / s to 300 m / s, from 0.12 m / s to 250 m / s, from 0.15 m / s to 200 m / s, from 0.17 m / s to 150 m / s, such as from 0.2 m / s to 100 m / s, from 0.4 m / s to 70 m / s, such as from 0.5 m / s to 60 m / s, from 0.7 m / s to 50 m / s, from 0.8 m / s to 40 m / s, from 0.9 m / s to 30 m / s, such as from 1 m / s to 20 m / s.

[0085] The viscosity of the coating composition for vacuum suction or deposition may be 0.1-8000 cPa, such as 0.5-7000 cPa, or 0.5-6000 cPa, or 0.5-5000 cPa, such as 0.5-4000 cPa, or 0.75-3000 cPa, such as 0.75-2000 cPa, or 0.75-1000 cPa, or 0.75-800 cPa, such as 1-700 cPa, or 1-600 cPa, preferably 1-500 cPa, or 1-250 cPa, 1-200 cPa, 1-100 cPa, or 2-80 cPa.

[0086] The surface tension of the coating composition may be 1 to 1000 mN / m, for example, 2 to 900 mN / m, or 3 to 800 mN / m, for example, 4 to 700 mN / m, or 5 to 600 mN / m, or 6 to 500, preferably 8 to 400 mN / m, or 9 to 300 mN / m, more preferably 10 to 200 mN / m, or 15 to 150 mN / m, or 25 to 100 mN / m.

[0087] The coating composition may be applied to a substrate such that the active layer is formed from one or more coating layers, either by repeating the coating process or by using a multi-coating process.

[0088] The coating layers may be coated from one or more of the same or different coating compositions.

[0089] The active layer may comprise multiple coating layers, where at least one of the layers has been treated prior to the deposition of a subsequent layer. Preferably, each layer has been treated prior to the deposition of a subsequent layer. The layers of the active layer comprising multiple coating layers may have been subjected to different treatments in terms of type and / or extent of treatment. Thus, at least one of the layers may comprise a two-dimensional material having a different functionality than the other layers. For example, the multiple layers may comprise a gradient of decreasing reduction level of the two-dimensional material from the top of the active layer adjacent to the substrate towards the bottom of the active layer. The gradient may be made in the opposite direction.

[0090] The presence of a gradient may enhance adhesion between the active layer and the substrate and may also enhance the fouling resistance of the overall film.

[0091] The gradient may be linear or varying, for example the level of treatment may first increase or decrease and then decrease or increase again, and may be in a regular or irregular pattern.

[0092] The altered gradient may improve the overall fouling resistance of the membrane. The altered gradient may also be able to selectively screen molecules.

[0093] 2D Material Processing The two-dimensional material on the substrate may be treated to alter the functional groups of the two-dimensional material, for example to change the number, type and / or distribution of functional groups. For example, treatment may reduce the two-dimensional material or functionalize the two-dimensional material by adding functionality to the two-dimensional material.

[0094] Treatment of a two-dimensional material to functionalize it may add or change functional groups of the two-dimensional material, for example, by reaction with existing hydroxyl, carboxyl and / or epoxy groups of the two-dimensional material. Functionalization includes covalent and non-covalent modification. Covalent modification methods can be classified into nucleophilic substitution reactions, electrophilic substitution reactions, condensation reactions, and addition reactions.

[0095] The two-dimensional material may be treated, preferably reduced, by exposing the two-dimensional material to radiation, such as laser radiation, microwave radiation, ultraviolet light, E-beam radiation, plasma treatment, electron beam, soft X-rays, gamma radiation, alpha radiation, chemical treatment and / or thermal treatment. Laser radiation and plasma treatment are preferred.

[0096] Chemically, thermally or radiation treating the 2D material on a substrate can be used to form chemically reduced GO (CRGO), thermally reduced graphene oxide (TRGO) or radiation reduced graphene oxide (RRGO).

[0097] The laser source used for treating two-dimensional materials with laser radiation may be selected from gas lasers, paramagnetic ion, chemical lasers, metal vapor lasers, dye lasers, free electron lasers, gas dynamic lasers, Raman lasers, nuclear pumped lasers, semiconductor lasers, solid state lasers, such as nitrogen lasers, helium neon lasers, argon lasers, krypton lasers, xenon ion lasers, carbon dioxide lasers, carbon monoxide lasers, excimer lasers, such as hydrogen fluoride lasers, deuterium lasers, chemical oxygen iodine lasers, all-vapor phase iodine lasers, such as stilbene lasers, coumarin lasers, rhodamine lasers, such as helium cadmium lasers, helium mercury lasers, helium selenium lasers, helium silver lasers, strontium vapor lasers, neon copper lasers, copper vapor lasers, gold vapor lasers, manganese lasers, such as ruby ​​lasers, Nd:YAG lasers, NdCrYAG lasers, Er:YAG lasers, neodymium Y The laser may be selected from LF solid state lasers, neodymium doped yttrium orthovanadate lasers, neodymium doped yttrium calcium oxoborate Nd:YCa4O(BO3)3 lasers, neodymium glass lasers, titanium sapphire lasers, thulium lasers, ytterbium lasers, ytterbium doped glass lasers, holmium YAG lasers, chromium ZnSe lasers, cerium doped lithium strontium (or calcium aluminum fluoride lasers), promethium 147 doped phosphate glass lasers, chromium doped chrysoberyl lasers, erbium doped and erbium ytterbium, trivalent uranium doped calcium fluoride solid state lasers, divalent samarium doped calcium fluoride lasers, F-center lasers such as semiconductor laser diode lasers, GaN lasers, InGaN lasers, AlGaInP lasers, AlGaAs lasers, lead salt lasers, vertical cavity surface emitting lasers, quantum cascade lasers, hybrid silicon lasers. Preferably, the laser is a gas laser, a paramagnetic ion laser, a chemical laser, a metal vapor laser, a dye laser, or a free electron laser.

[0098] The wavelength of the laser radiation may be from 150 nm to 360,000 nm, for example from 150 nm to 300,000 nm, from 155 nm to 250,000 nm, for example from 150 nm to 200,000 nm, for example from 162 nm to 150,000 nm, for example from 165 nm to 100,000 nm, for example from 166 nm to 80,000 nm, from 170 nm to 60,000 nm, for example from 175 nm to 45,000 nm, for example from 176 nm to 35 ,000 nm, for example, 177 nm to 25,000 nm, for example, 178 nm to 20,000 nm, 179 nm to 15,000 nm, 180 nm to 10,000 nm, 182 nm to 5,000 nm, 183 nm to 3,500 nm, for example, 185 nm to 3,000 nm, 188 nm to 2,000 nm, 189 nm to 1,000 nm, for example, 190 nm to 900 nm, or 192 nm to 650 nm.

[0099] The intensity of the laser radiation is 1×10 5 W / cm 2 ~1×10 29 W / cm 2 , e.g. 5×10 5 W / cm 2 and 1×10 28 W / cm 2 , 1×10 6 W / cm 2 and 1×10 27 W / cm 2 , 1×10 6 W / cm 2 and 1×10 26 W / cm 2 , e.g. 5×10 6 W / cm 2 and 1×10 25 W / cm 2 , 1×10 7 W / cm 2 and 1×10 24 W / cm 2 , 5×10 7 W / cm 2 and 1×10 23 W / cm 2 , e.g. 1×10 8 W / cm 2 and 1×10 22 W / cm 2 , 5×108 W / cm 2 and 1×10 21 W / cm 2 , e.g. 1×10 9 W / cm 2 and 1×10 20 W / cm 2 It may be in the range.

[0100] The number of laser scans may be 1 and 1000, e.g. 1 and 900, 1 and 800, 1 and 700, 1 and 600, 1 and 500, 1 and 400, 1 and 300, 1 and 200, 1 and 100, 1 and 90, 1 and 80, 1 and 70, 1 and 60, 1 and 50, 1 and 40, 1 and 35, 1 and 30, e.g. 1 and 25, 1 and 20, e.g. 1 and 15.

[0101] The laser scanning speed may be 0.1 mm / s to 1000 mm / s, for example, 0.5 mm / s to 900 mm / s, 1 mm / s to 850 mm / s, 1.5 mm / s to 800 mm / s, 2 mm / s to 750 mm / s, 2.5 mm / s to 700 mm / s, for example, 3 mm / s to 650 mm / s, 5 mm / s to 600 mm / s, 6 mm / s to 550 mm / s, for example, 7 mm / s to 500 mm / s, 8 mm / s to 450 mm / s, 8.5 mm / s to 400 mm / s, for example, 9 mm / s to 350 mm / s, 10 mm / s to 300 mm / s, for example, 11 mm / s to 250 mm / s.

[0102] The laser energy density (fluence) is 0.001J / cm 2 ~100J / cm 2 , e.g. 0.003 J / cm 2 ~90J / cm 2 , 0.005J / cm 2 ~85J / cm 2 , 0.007J / cm 2 ~80J / cm 2 , 0.01J / cm 2 ~75J / cm 2 , 0.02J / cm 2 ~70J / cm 2 , 0.03J / cm 2 ~65J / cm2 , e.g. 0.04 J / cm 2 ~60J / cm 2 , 0.05J / cm 2 ~55J / cm 2 , 0.055J / cm 2 ~50J / cm 2 , e.g. 0.06 J / cm 2 ~45J / cm 2 , 0.065J / cm 2 ~40J / cm 2 , e.g. 0.07 J / cm 2 ~35J / cm 2 Or 0.07~30J / cm 2 may be also possible.

[0103] The pulse length of the laser radiation can be from femtosecond to nanosecond, microsecond or continuous wave.

[0104] The diameter or width of the laser beam may be in the range of 0.1 nm to 1 cm, for example 0.5 nm to 0.7 cm, 1 nm to 0.5 cm, 5 nm to 0.2 cm, for example 10 nm to 0.1 cm, 15 nm to 500 μm, 16 nm to 700 μm, 17 nm to 100 μm, 18 nm to 80 μm, for example 20 nm to 15 μm.

[0105] The laser radiation may be performed in an ambient atmosphere, a vacuum, or an atmosphere of an inert gas such as nitrogen, helium, argon, or carbon dioxide.

[0106] The two-dimensional material on the substrate may be subjected to a chemical treatment, preferably to reduce the two-dimensional material.

[0107] To reduce the two-dimensional material on the substrate, a solution of reducing agent may be used. The chemical solution may contain a treating agent preferably selected from H2O2, NaOH and / or hydrazine (N2H4), ascorbic acid, sodium bicarbonate, sodium borohydride, sodium borohydride, hydrochloric acid, melatonin, polyphenols, vitamin C, hydroiodic acid, trifluoroacetic acid, sulfur-containing compounds such as Na2SO3, NaHSO3, NaS2O3, Na2S9H2O, SOCl2, and SO2, preferably hydrazine, sodium borohydride and / or ascorbic acid.

[0108] The concentration of the treating agent in the solution depends on the treating agent selected. For example, the amount of treating agent such as H2O2, NaOH and / or N2H4 in the water may range from 0.01% to 90% by weight, such as 0.05% to 85% by weight, 0.09% to 80% by weight, 0.1% to 75% by weight, such as 0.5% to 70% by weight, 0.9% to 65% by weight, 1% to 60% by weight, 1.5% to 55% by weight, 1.7% to 50% by weight, such as 2% to 45% by weight, 2.5% to 40% by weight, 2.7% to 35% by weight, such as 3% to 30% by weight, based on the total weight of the solution.

[0109] The treatment agent may be added to the coating composition prior to application of the coating composition to a substrate.

[0110] The temperature for the treatment may be from 0 to 200°C, for example from 10 to 150°C, for example from 15 to 120°C, or from 16 to 110°C, for example from 17 to 100°C, for example from 18 to 90°C, preferably from 19 to 90°C.

[0111] Suitably, the treatment of the two-dimensional material may involve passing a treatment agent through a membrane and / or impregnating the membrane with the treatment agent.

[0112] The treatment may comprise or consist of a heat treatment, such as hydrothermal, applied to the treatment of the coating composition or the film after coating. The heat treatment may be applied under an inert atmosphere, such as nitrogen, and / or at a temperature of at least 80°C, such as at least 100°C, for example from 100°C to 800°C, for example from 100°C to 700°C, from 100°C to 500°C, from 100°C to 400°C, from 100°C to 500°C, preferably from 100°C to 450°C.

[0113] Advantageously, the treated membrane may provide improved performance such as improved selective sieving, improved size exclusion, improved ion removal, improved removal rate such as compound removal, oil removal, bacteria removal, virus removal, cyst removal, etc., e.g., improved transport rate.

[0114] The characteristics of the processed two-dimensional material may be according to any one or more of the characteristics as defined above in relation to the two-dimensional material of the coating composition, i.e. in relation to the two-dimensional material in pre-processed form, e.g. with regard to the type of two-dimensional material, the morphology of the two-dimensional material, the d-spacing of the two-dimensional material, the size distribution of the two-dimensional material, and / or the atomic content of the two-dimensional material.

[0115] Advantageously, the treated membrane can be tailored to a desired hydrophilicity and / or to enhance the electrical and / or thermal conductivity of the membrane.

[0116] The hydrophilicity of the treated membrane may be controlled by the proportion of functional groups or polar atoms such as oxygen or nitrogen that remain on the surface after treatment.

[0117] Hydrophilicity can be empirically quantified using X-ray photoelectron spectroscopy to calculate the number of functional groups remaining in the treated 2D material, or by measuring the proportion of polar atoms such as oxygen or nitrogen, according to methods known to those of skill in the art.

[0118] The oxygen or nitrogen atomic content of the 2D material, preferably the laser treated 2D material, may be between 0% and 65%, such as between 0.5% and 50%, between 0.8% and 48%, between 1% and 49%, between 1.2% and 46%, between 1.5% and 45%, such as between 1.8% and 44%, between 2.0% and 44%, between 2.2% and 44%, between 2.2% and 43%, such as between 2.5% and 43%, between 3.0% and 43%, such as between 3.5% and 43% or between 10 and 43%.

[0119] The processed two-dimensional material may have a thermal conductivity of 0.1 W / mK to 6,000 W / mK, e.g., 1 W / mK to 5,500 W / mK, 1.5 W / mK to 5,000 W / mK, e.g., 2 W / mK to 4,500 W / mK, 2.5 W / mK to 4,100 W / mK, 3 W / mK to 3,800 W / mK, e.g., 3.5 W / mK to 3,300 W / mK, 4 W / mK to 3,000 W / mK / mK, for example, 4.5 W / mK to 2,500 W / mK, 5 W / mK to 2,000 W / mK, 5.5 W / mK to 1,700 W / mK, for example, 6 W / mK to 1,500 W / mK, 6.5 W / mK to 1,300 W / mK, 7 W / mK to 1,100 W / mK, 8 W / mK to 900 W / mK, or 9 W / mK to 800 W / mK.

[0120] The processed two-dimensional material preferably has a thermal conductivity of between 9 W / mK and 800 W / mK.

[0121] The processed two-dimensional material has a density of 1×10 -6 S / m~600,000S / m, e.g. 5×10 -6 S / m~300,000S / m, 8×10 -6 S / m~100,000S / m, 1×10 -5 S / m to 50,000S / m, e.g. 3×10 -5 S / m~28,000S / m, 8×10 -5 S / m~25,000S / m, 1×10 -4 S / m~24,000S / m, e.g. 3×10 -4 S / m~23,000S / m, 5×10 -4 S / m~20,000S / m, 1×10 -3 S / m~17,000S / m, 5×10 -3S / m to 14,000S / m, e.g. 1×10 -2 S / m~10,000S / m, 5×10 -2 The conductive material may have an electrical conductivity in the range of 0.1 S / m to 8,000 S / m, for example, 0.1 S / m to 7,000 S / m, or 1 S / m to 6,000 S / m.

[0122] Preferably, the treated functionalized two-dimensional material has a higher number of at least one type of functional group than the two-dimensional material before treatment. The functionalized treated two-dimensional material may have a higher number of amino groups; long chain (e.g., C 16 ~C 50 aliphatic amino groups such as aliphatic amino groups of 1,2-diaminopropyltriethoxysilane; porphyrin-functionalized secondary amino groups, and / or 3-aminopropyltrialkoxysilane groups such as 3-aminopropyltriethoxysilane groups. Preferably, the amino-functionalized treated 2D material is an amino-functionalized treated graphene oxide. Such functionalization can result in improved selective sieving of ferric acid. The functionalized treated 2D material may be formed from the treatment of graphene oxide (GO) utilizing existing -COOH, -OH, and COC groups.

[0123] The functionalized treated graphene or its derivatives may be: amino-based graphene (such as by addition of CONH(CH2)NH2, NH2-TTP, alkylamine functionalized GO, and / or ammonia functionalized graphene oxide), isocyanate modified GO (such as -CO-NHR groups), octadecylamine functionalized reduced graphene oxide, polymeric graphene aerogel, azide, alkyne functionalized GO, poly(allylamine) modified, DNA or protein modified (non-covalently), etc. The functionalized treated graphene or its derivatives may include functional groups attached towards the edges of the two-dimensional material, such as NO2, -NH2, -SO3H, halide, -N3, -MgBr and / or -SH groups. Suitably, the functionalized treated graphene or its derivatives includes more such groups towards the edges of the platelets compared to untreated graphene or its derivatives. The active layer may include polymers such as polystyrene and / or polyethersulfone, and / or functionalized reduced graphene oxide with restored π-π interactions that result in non-covalent bonding with small molecules such as pyrene and its derivatives, tetracyanoquinodimethane, perylene derivatives, and / or other aromatic species.

[0124] The thickness of the active layer may be at least 0.5 nm, for example at least 0.7 nm or at least 0.9 nm. The active layer may have a thickness of 1 nm to 8000 nm, for example 2 to 5000 nm, or 3 to 4000 nm, for example 4 to 3000 nm, or 5 to 2000 nm, or 5 to 1000 nm, or 10 to 500 nm, for example 10 to 400 nm, or 10 to 200 nm, preferably 10 to 100 nm or 5 to 60 nm.

[0125] Preferably, said active layer is formed substantially from a two-dimensional material, suitably from graphene or a derivative thereof, more preferably from processed graphene or a derivative thereof.

[0126] The amount of two-dimensional material in the active layer or in each coating layer may be at least 1% by weight, or at least 5% by weight, such as 5-100% by weight, for example 10-100% by weight, 15-99% by weight, 20-99.9% by weight, 20-99.8% by weight, 50-99.7% by weight, 80-99.7% by weight, preferably 85-99.7% by weight.

[0127] The active layer may contain additives to tailor the properties of the active layer, such as other metals and / or fibers, such as metal oxide fibers, such as nanostrands and / or dopants, such as Au, Fe, Cu, Cu(OH)2, Cd(OH)2, and Zr(OH)2. Such additives may affect the interlayer distance and / or form micro- or nano-channels for high water transport rates.

[0128] The active layer may further comprise micro- or nano-channels suitably formed by the use and subsequent removal of fibers during the manufacture of the membrane and / or by processing of the two-dimensional material. Advantageously, the presence of micro- and / or nano-channels in the active layer has been found to significantly increase the water flux and improve the anti-fouling properties of the membrane.

[0129] The processed portion of the two-dimensional material may be the entire two-dimensional material or a portion of the two-dimensional material. For example, an active layer may include two-dimensional material processed on at least one coating layer, on at least one coating layer, through at least one coating layer, and / or through the entire active layer. Partial processing of the two-dimensional material may be used to form channels, such as microchannels or nanochannels, which may be in the form of closed or open loops, electronic circuit patterns, grids, and / or artistic patterns.

[0130] The nanochannels or microchannels may have a diameter of 0.1 to 1000 nm, for example, 0.1 to 850 nm, 0.2 to 750 nm, 0.3 to 500 nm, or 0.4 to 250 nm, or 0.45 to 150 nm, or 0.45 to 100 nm, or 0.45 to 75 nm, preferably 0.45 to 50 nm, or 0.45 to 10 nm, preferably 0.45 to 5 nm.

[0131] The presence of nanochannels may increase the transport rate by at least 50%, such as 100%, or 150%, or 500%, or 1000%, compared to an active layer that does not include nanochannels.

[0132] The presence of micro- and / or nano-channels in the active layer can provide features such as electrical and thermal conductivity that can be used to monitor the lifetime or failure of the membrane. For example, membrane failure may be detectable by damage to the conductive channel causing a change in the magnitude of the voltage or current in that portion of the channel.

[0133] The thickness of the active layer deposited on a substrate by deposition (vapor deposition) may be controlled by using a constant concentration of the composition, for example 100 ml of 0.001 mg / ml.

[0134] The membranes of the present invention may be for any type of separation. Suitably, the membranes are for water separation, such as desalination or oil-water separation, or for chemical separation.

[0135] Chlorides can be harmful to polymeric substrates, and the coated membrane can sieve the chlorides and reduce their contact with the polymeric substrate, potentially extending the substrate's lifespan.

[0136] As used herein, the term "lamellar structure" refers to a structure having at least two overlapping layers. As used herein, the term "active layer" refers to a layer operable to provide separation across the layer. As used herein, the term "two-dimensional material" refers to a material having at least one dimension less than 100 nm.

[0137] As used herein, the term aliphatic refers to a hydrocarbon moiety that may be linear, branched, or cyclic, may be fully saturated, or may contain one or more unsaturated units, but is not aromatic. The term "unsaturated" refers to a moiety having one or more double and / or triple bonds. Thus, the term "aliphatic" is intended to include alkyl, cycloaliphatic, alkenyl, or alkynyl groups. The aliphatic group preferably contains 1 to 15 carbon atoms, for example, 1 to 14 carbon atoms, 1 to 13 carbon atoms, i.e., an aliphatic group having 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, or 13 carbon atoms.

[0138] The alkyl group contains 1 to 15 carbon atoms. The alkyl group may be linear or branched. The alkyl group preferably contains 1 to 14 carbon atoms, 1 to 13 carbon atoms, i.e., alkyl groups having 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 carbon atoms. Specific examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, 1-ethylpropyl, n-hexyl, 1-ethyl-2-methylpropyl, 1,1,2-trimethylpropyl, 1-ethylbutyl, 1-methylbutyl, 2-methylbutyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 2,2-dimethylbutyl, 1,3-dimethylbutyl, 2,3-dimethylbutyl, 2-ethylbutyl, 2-methylpentyl, 3-methylpentyl, and the like, and isomers thereof.

[0139] The alkenyl and alkynyl groups each contain 2 to 12 carbon atoms, such as 2 to 11 carbon atoms, 2 to 10 carbon atoms, such as 2 to 9, 2 to 8 or 2 to 7 carbon atoms. Such groups may contain two or more carbon-carbon unsaturated bonds.

[0140] The alicyclic group may be a saturated or partially unsaturated cycloaliphatic monocyclic or polycyclic (including fused, bridged and spiro-fused) group having 3 to 15 carbon atoms, for example 3 to 14 carbon atoms or 3 to 13 carbon atoms, i.e. an alicyclic group having 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 carbon atoms. Preferably, the alicyclic group has 3 to 12, more preferably 3 to 11, even more preferably 3 to 10, even more preferably 3 to 9 carbon atoms, or 3 to 8 carbon atoms, or 3 to 7 or 3 to 6 carbon atoms. The term "alicyclic" encompasses cycloalkyl groups, cycloalkenyl groups and cycloalkynyl groups. It will be understood that the alicyclic group may include an alicyclic ring having one or more linked or unlinked alkyl substituents, such as -CH2-cyclohexyl. Specifically, C 3~15 Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, adamantyl, isobornyl, and cyclooctyl.

[0141] The aryl group is a monocyclic or polycyclic group having 6 to 14 carbon atoms, for example 6 to 13 carbon atoms, 6 to 12 carbon atoms, or 6 to 11 carbon atoms. The aryl group is preferably defined as "C 6~12 An aryl group is an aryl group consisting of 6, 7, 8, 9, or 10 carbon atoms, including monocyclic and fused ring groups such as bicyclic ring groups. 6~10 Examples of "aryl groups" include phenyl, biphenyl, indenyl, naphthyl, or azulenyl, etc. It should be noted that fused rings such as indane and tetrahydronaphthalene are also included in the aryl group.

[0142] The use of the term "hetero" in heteroaliphatic and heteroaryl is well known in the art. Heteroaliphatic and heteroaryl refer to an aliphatic or aryl group, as defined herein, in which one or more carbon atoms in the chain and / or ring of the group are replaced with a heteroatom. The heteroatom may be one or more of sulfur and / or oxygen.

[0143] The heteroatom(s) may be in any form that does not remove the ability of the amine group of the multifunctional amine to react with the multifunctional amine reactive. The heteroatom(s) may be any form that does not remove the ability of the amine group of the multifunctional amine to react with the multifunctional amine reactive. 15 It may be in the form of an ether group, such as an alkoxy; a hydroxyl group if terminal; a heterocycle of sulfur and oxygen; and / or a polysulfide group, such as a polysulfide containing at least two sulfur atoms.

[0144] Preferably, the alkoxy group contains 1 to 8 carbon atoms and is suitably selected from methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, and isomers thereof.

[0145] As used herein, unless expressly specified otherwise, all numbers, such as numbers expressing values, ranges, amounts, or percentages, may be read as if preceded by the word "about" even if the word "about" does not appear explicitly. "About" may be defined as ±10% of the stated value. Also, all numerical ranges described herein are intended to include all subranges contained therein. The singular encompasses the plural and vice versa. For example, although reference is made herein to "a" substrate, "an" active layer, "a" coating composition, "a" two-dimensional material, etc., one or more of each of these components, as well as any other components, may be used. As used herein, the term "polymer" refers to both oligomers and homopolymers and copolymers, and the prefix "poly" means two or more. For example, including and similar terms mean, for example, including but not limited to. Additionally, although the invention has been described in terms "comprising...", the processes, materials, and aqueous coating compositions detailed herein may be described as "consisting essentially of..." or "consisting of...".

[0146] All features contained herein may be combined with any of the above aspects in any combination.

[0147] For a better understanding of the present invention and to show how embodiments thereof may be practiced, reference will now be made by way of illustration to the following examples. EXAMPLES

[0148] Example 1 – Preparation of reduced graphene oxide films by multilayer coating with different graphene-based materials An ink containing 1 mg / ml of graphene oxide with an oxygen atom content of 40% was coated onto a polysulfone substrate with a pore size of 25 nm using flexographic coating technology, with the coating thickness being approximately 20 nm. After drying at room temperature and pressure, another ink containing 1 mg / ml of reduced graphene oxide with an oxygen atom content of 10% was coated onto the surface of the coated graphene oxide from above using flexographic coating, with the coating thickness being approximately 20 nm. The performance of the resulting film was then evaluated, and it was found to have a 100% longer life and a 50% increase in dye molecule removal rate compared to when only reduced graphene oxide was coated.

[0149] Example 2 – Substrate treatment and preparation of reduced graphene oxide films using different graphene-based materials A polysulfone substrate with a pore size of 25 nm was immersed in 0.25 M NaOH for 20 minutes, washed with deionized water, and dried at 40 °C for 1 hour. Next, an ink containing 1 mg / ml of graphene oxide with an oxygen atom content of 40% was coated on the substrate using flexo-coating technology. The thickness of the coating is about 20 nm. After drying at room temperature and pressure, another ink containing 1 mg / ml of reduced graphene oxide with an oxygen atom content of 10% was coated on the surface of the coated graphene oxide from above using flexo-coating technology. The thickness of the coating is about 20 nm. The performance of the obtained membrane was then evaluated, and it was found that the life span was improved by 200% and the dye molecule removal rate was improved by 50% compared to the case where only reduced graphene oxide was coated.

[0150] Example 3 – Preparation of reduced graphene oxide films by post-treatment method A polysulfone substrate with pore size of 25 nm was immersed in 0.25M NaOH for 20 minutes, then washed with deionized water and dried at 40°C for 1 hour. An ink containing 1 mg / ml of graphene oxide with 40% oxygen atom content was then coated onto the substrate using flexo-coating technique. The coating thickness was approximately 40 nm. After drying at room temperature and pressure, the coated surface was immersed in 0.1 M aqueous sodium borohydride solution for 0.5 hours. The performance of the resulting membrane was then evaluated and found to exhibit 60% dye molecule removal rate compared to 0% for the uncoated substrate.

[0151] Example 4 - Preparation of separation membrane by post-treatment A polysulfone substrate with a pore size of 25 nm was immersed in 0.25 M NaOH for 20 minutes, then washed with deionized water and dried at 40 °C for 1 hour. An ink containing 1 mg / ml of graphene oxide with an oxygen atom content of 40% mixed with 0.5 mg / ml of Cu(OH)2 nanostrands with a diameter of 2 nm and a length of 1 μm was then coated onto the substrate using flexocoating technology, with the coating thickness being approximately 100 nm. After drying at room temperature and pressure, the coated surface was immersed in 0.1 M sodium borohydride aqueous solution for 0.5 hours to reduce the graphene oxide, and filtered with 0.15 M ethylenediaminetetraacetic acid to dissolve the nanostrands and form nanochannels. The performance of the resulting membrane was then evaluated, and it was found to have a significant improvement in transport rate of at least 300% and dye molecule removal rate of 40% compared to a membrane coated with graphene oxide.

[0152] Attention is directed to all papers and documents filed contemporaneously or prior to this application in connection with this application and published herewith, and the contents of all such papers and documents are incorporated herein by reference.

[0153] All of the features disclosed in this specification (including the accompanying claims, abstract and drawings), and / or all of the steps of any method or process so disclosed, may be combined in any combination, except combinations in which at least some of such features and / or steps are mutually exclusive.

[0154] Each feature disclosed in this specification (including the accompanying claims, abstract and drawings), unless expressly stated otherwise, may be replaced by alternative features serving the same, equivalent or similar purpose. Thus, unless expressly stated otherwise, each feature disclosed is only an example of a generic series of equivalent or similar features.

[0155] The invention is not limited to the details of the embodiments described above, and extends to any novel one or any novel combination of features disclosed in this specification (including the accompanying claims, abstract and drawings), or to any novel one or any novel combination of method or process steps so disclosed.

Claims

1. According to a first aspect of the present invention, there is provided a separation membrane, preferably for water separation, comprising a porous substrate layer and an active layer disposed on at least a portion of said substrate layer, said active layer comprising a lamellar structure comprising at least two layers of processed two-dimensional material.

2. A method for producing a separation membrane, preferably a membrane according to claim 1, comprising the steps of: a. optionally preparing a substrate, optionally by treating said substrate with a chemical treatment and / or a radiation treatment and / or a plasma treatment and / or a heat treatment; b. contacting said substrate with a composition comprising a two-dimensional material, optionally by forming a first layer of a composition comprising a two-dimensional material, and then applying a further layer of said composition comprising a two-dimensional material to said first layer, which layer may optionally be dried before application of a subsequent layer; c. Optionally, drying the membrane; d. Treating the two-dimensional material applied in step (b) to cause a change in the functional groups of the two-dimensional material, such as by applying high energy radiation, such as laser radiation, chemicals, high temperature, thermal energy and / or pressure to the two-dimensional material, optionally by treating the first layer of composition prior to application and subsequent treatment of further layers of the composition; e. Optionally, drying the membrane. The method includes:

3. Preferably, the separation membrane for water separation comprises a porous substrate layer and an active layer disposed on at least a portion of the substrate layer, the active layer comprising at least two coating layers each comprising a two-dimensional material, and at least one of the coating layers of the active layer is different from another coating layer of the active layer.

4. A method for producing a separation membrane, preferably a membrane according to claim 1 or claim 3, comprising the steps of: a. optionally preparing a substrate, optionally by treating said substrate with a chemical treatment and / or a radiation treatment and / or a plasma treatment and / or a heat treatment; b. contacting the substrate with a composition comprising a two-dimensional material to form a first coating layer; c. applying one or more further coating layers of one or more compositions comprising a two-dimensional material to said first layer, optionally drying one or more of said layers between the application of subsequent layers; d. Optionally, drying the membrane. wherein at least one of the plurality of coating layers is different from another coating layer.

5. The membrane of claim 1 or claim 3, wherein the active layer comprises nanochannels having a diameter of 1 to 100 nm.

6. A method for producing a separation membrane, preferably a membrane according to claim 1, claim 3 or claim 5, comprising the steps of: a. optionally providing a substrate; b. contacting the substrate with a coating composition comprising a two-dimensional material and nanofibers; c. removing the nanofibers by contacting the membrane produced by step (b) with a weak acid, for example an acid having a pH between 1 and 6; d. treating, preferably reducing, said two-dimensional material, preferably by laser treatment, chemical treatment and / or thermal treatment; e. Optionally, drying the membrane. The method includes:

7. 10. The membrane of claim 1, claim 3 or claim 5, wherein the substrate comprises a polymeric substrate, a polymeric substrate with inorganic filler, a ceramic substrate, a composite substrate, a metallic substrate such as a thin film composite substrate, an inorganic substrate, an inorganic-organic substrate, a metal substrate, a woven filament such as a woven monofilament or a woven multifilament, and / or a non-woven substrate, and / or a cast substrate.

8. 8. The membrane of claim 1, claim 3, claim 5 or claim 7, wherein the substrate is in the form of a porous film, a porous plate, a porous hollow fiber substrate, a tubular fiber substrate, a bulky porous material, preferably in the form of a film.

9. 9. The membrane of claim 1, claim 3, claim 5, claim 7 or claim 8, wherein the polymer substrate is selected from one or more of polyamide (PA), polysulfone (PSf), polyvinylidene fluoride (PVDF), and thin film composites (TFCs) such as polysulfone supported polyamide composite substrates.

10. The membrane according to any one of claims 1, 3, 5 and 7 to 9, wherein the average size of the pores of the substrate may be from 0.1 nm to 30,000 nm, preferably from 200 nm to 5000 nm.

11. The membrane of any one of claims 1, 3, 5, and 7 to 10, wherein the active layer is formed from a coating composition comprising the two-dimensional material.

12. 12. The membrane or method of any one of claims 1 to 11, wherein the coating composition comprises a two-dimensional material together with a carrier and / or additives.

13. 13. The membrane or method of any one of claims 1 to 12, wherein the two-dimensional material comprises one or more of graphene or derivatives thereof, silicene, germanene, stanene, boron nitride, preferably h-boron nitride, carbon nitride, metal-organic nanosheets, polymers, graphene aerogels, two-dimensional metal-organic frameworks, three-dimensional metal-organic frameworks, and / or transition metal dichalcogenides and their derivatives.

14. 14. The membrane or method of any one of claims 1 to 13, wherein the two-dimensional material comprises graphene or a derivative thereof.

15. 15. The membrane or method of any one of claims 1 to 14, wherein the graphene or derivative thereof is selected from one or more of graphene oxide, reduced graphene oxide from graphene oxide, reduced graphene oxide by a bottom-up process, oxidized graphene by processing from graphite, functionalized graphene, functionalized graphene oxide, functionalized reduced graphene oxide, and / or functionalized oxidized graphene, composites thereof, and dispersions thereof.

16. 16. The membrane or method of any one of claims 1 to 15, wherein the graphene or derivatives thereof are selected from one or more of graphene oxide, reduced graphene oxide, hydrated graphene, amino-based graphene, alkylamine-functionalized graphene oxide, ammonia-functionalized graphene oxide, amine-functionalized reduced graphene oxide, octadecylamine-functionalized reduced graphene oxide, hydrazide-functionalized graphene, hydrazine-functionalized graphene, amide-functionalized graphene, amine-PEG-functionalized graphene, graphene composites, and / or polymeric graphene aerogels.

17. 17. The membrane or method of any one of claims 1 to 16, wherein the graphene or derivative thereof is graphene oxide.

18. 18. The membrane or method according to any one of the preceding claims, wherein the oxygen atomic content of the two-dimensional material is in the range of 1% to 60%, such as 2% to 50%, for example 3% to 45%, or 5% to 44%, or 10% to 44%, preferably 15% to 44%.

19. The composition is preferably Cu(OH) 2 , Cd(OH) 2 and Zr(OH) 2 19. A membrane or method according to any one of claims 1 to 18, comprising fibres, preferably in the form of metal oxide nanostrands, selected from one or more of:

20. 20. The membrane or method of any one of claims 1 to 19, wherein the coating composition is coated onto the substrate using bar coating, flexographic coating, inkjet printing, screen coating or slot coating.

21. 21. A membrane or method according to any one of claims 1 to 20, wherein the active layer may comprise multiple coating layers, preferably at least one of the multiple layers being treated prior to application of a subsequent layer.

22. 22. The membrane or method of any one of claims 1 to 21, wherein the coating layer of the active layer comprises a gradient of decreasing, increasing or varying reduction levels across the active layer within the two-dimensional material.

23. 23. The membrane or method according to any one of claims 1 to 22, wherein the two-dimensional material is treated, preferably reduced, by exposing the two-dimensional material to radiation such as laser radiation, microwave radiation, ultraviolet light, E-beam radiation, plasma treatment, electron beam, soft X-rays, gamma rays, alpha rays, chemical treatment, pressure treatment and / or heat treatment, preferably laser radiation and / or plasma treatment.

24. 24. The membrane or method according to any one of claims 1 to 23, wherein the two-dimensional material is treated, preferably reduced, by exposing the two-dimensional material to laser radiation, preferably a gas laser, a paramagnetic ion laser, a chemical laser, a metal vapor laser, a dye laser, or a free electron laser.

25. The two-dimensional material is preferably 2 O 2 , NaOH and / or hydrazine (N 2 H 4 ), Ascorbic Acid, Sodium Bicarbonate, Sodium Borohydride, Sodium Borohydride, Hydrochloric Acid, Melatonin, Polyphenols, Vitamin C, Hydroiodic Acid, Trifluoroacetic Acid, Na 2 SO 3 , NaHSO 3 , NaS 2 O 3 , Na 2 S9H 2 O, SOCl 2 , and S.O. 2 25. The membrane or method according to any one of claims 1 to 24, wherein the membrane is treated, suitably reduced, by subjecting it to a chemical treatment by application of a treating agent such as sulphur-containing compounds such as sulphur ions, preferably hydrazine, sodium borohydride and / or ascorbic acid.

26. 26. The membrane or method according to any one of claims 1 to 25, wherein the two-dimensional material is treated, suitably reduced, by subjecting the two-dimensional material to a heat treatment, such as hydrothermal, applied to the coating composition or to the treatment of the membrane after coating, preferably the heat treatment is applied under an inert atmosphere, such as nitrogen, and / or at a temperature of at least 80°C, such as at least 100°C, for example from 100°C to 800°C, for example from 100°C to 700°C, from 100°C to 500°C, from 100°C to 400°C, from 100°C to 500°C, preferably from 100°C to 450°C.

27. 27. The membrane or method according to any one of the preceding claims, wherein the oxygen and / or nitrogen atomic content of the treated 2D material is between 0% and 65%, such as between 0.5% and 50%, between 0.8% and 48%, between 1% and 49%, between 1.2% and 46%, between 1.5% and 45%, such as between 1.8% and 44%, between 2.0% and 44%, between 2.2% and 44%, between 2.2% and 43%, such as between 2.5% and 43%, between 3.0% and 43%, preferably between 3.5% and 43% or between 10 and 43%.

28. 28. The membrane or method of any one of claims 1 to 27, wherein the active layer comprises a first layer comprising a two-dimensional material having a first oxygen content and a second layer comprising a two-dimensional material having a second oxygen content, the first and second oxygen contents being different.

29. 29. The membrane or method of any one of the preceding claims, wherein said first oxygen content is from 30 to 50% and said second oxygen content is from 1 to 30%.

30. 30. The membrane or method of any one of claims 1 to 29, wherein a layer comprising a first oxygen content is disposed between the substrate and the second layer comprising the second oxygen content.

31. The treated two-dimensional material may have a thermal conductivity of 0.1 W / mK to 6,000 W / mK, for example 1 W / mK to 5,500 W / mK, 1.5 W / mK to 5,000 W / mK, for example 2 W / mK to 4,500 W / mK, 2.5 W / mK to 4,100 W / mK, 3 W / mK to 3,800 W / mK, for example 3.5 W / mK to 3,300 W / mK, 4 W / mK to 3,000 W / mK, for example 4.5 W / mK to 2,500 31. The film or method of any one of claims 1 to 30, having a thermal conductivity in the range of 5 W / mK to 2,000 W / mK, 5.5 W / mK to 1,700 W / mK, preferably 6 W / mK to 1,500 W / mK, 6.5 W / mK to 1,300 W / mK, more preferably 7 W / mK to 1,100 W / mK, 8 W / mK to 900 W / mK, most preferably 9 W / mK to 800 W / mK.

32. The processed two-dimensional material has a thickness of 1×10 -6 S / m to 600,000 S / m, for example 5×10 -6 S / m~300,000S / m, 8×10 -6 S / m~100,000S / m, 1×10 -5 S / m to 50,000 S / m, for example 3×10 -5 S / m~28,000S / m, 8×10 -5 S / m~25,000S / m, 1×10 -4 S / m to 24,000 S / m, for example 3×10 -4 S / m~23,000S / m, 5×10 -4 S / m to 20,000 S / m, preferably 1×10 -3 S / m~17,000S / m, 5×10 -3 S / m to 14,000 S / m, more preferably 1×10 -2 S / m~10,000S / m, 5×10 -2 32. The membrane or method of any one of the preceding claims, having an electrical conductivity in the range of from 0.1 S / m to 7,000 S / m, such as from 0.1 S / m to 7,000 S / m, most preferably from 1 S / m to 6,000 S / m.

33. The treated two-dimensional material may have amino groups; long chain (e.g., C 16 ~C 50 33. The membrane or method of any one of claims 1 to 32, comprising aliphatic amino groups such as aliphatic amino groups of formula (I); porphyrin-functionalized secondary amino groups, and / or 3-aminopropyltrialkoxysilane groups such as 3-aminopropyltriethoxysilane groups, preferably wherein the amino-functionalized treated two-dimensional material is amino-functionalized treated graphene oxide.

34. The processed two-dimensional material is amino-based graphene (CONH(CH 2 ) N.H. 2 , N.H. 2 34. The membrane or method of any one of claims 1 to 33, comprising modified graphene oxide, isocyanate modified GO, (such as by addition of -TTP, alkylamine functionalized GO, and / or ammonia functionalized graphene oxide), isocyanate modified GO, (such as -CO-NHR groups), octadecylamine functionalized reduced graphene oxide, polymeric graphene aerogel, azide-, alkyne functionalized GO, poly(allylamine) modifications, DNA or protein modifications (non-covalently bound).

35. The treated two-dimensional material is 2 , -NH 2 , -SO 3 H, halide, -N 3 35. The membrane or method of any one of claims 1 to 34, comprising functional groups attached towards the edges of the 2D material, such as -MgBr and / or -SH groups, preferably the functionalized treated 2D material comprises more of such groups towards the edges of the platelets compared to untreated 2D material.

36. 36. A membrane or method according to any one of claims 1 to 35, wherein the active layer comprises micro- or nano-channels suitably formed by using and subsequently removing fibres during the manufacture of the membrane and / or by processing the two-dimensional material.

37. 37. A membrane or method according to any one of claims 1 to 36, wherein the processing of the two-dimensional material forms channels, such as microchannels or nanochannels, which channels are in the form of closed or open loops, electronic circuit patterns, grids and / or artistic patterns.

38. 38. The membrane or method of any one of the preceding claims, wherein the nano- or microchannels may have a diameter of 0.1 to 1000 nm, such as 0.1 to 850 nm, 0.2 to 750 nm, 0.3 to 500 nm, preferably 0.4 to 250 nm, or 0.45 to 150 nm, or 0.45 to 100 nm, 0.45 to 75 nm, more preferably 0.45 to 50 nm or 0.45 to 10 nm, most preferably 0.45 to 5 nm.

39. 39. The membrane or method according to any one of claims 1 to 38, wherein the membrane is for oil / water separation, molecular separation, pharmaceutical separation to remove pharmaceutical residues in an aquatic environment, drug separation, biofiltration, e.g. separation of microorganisms and water, desalination, preferably seawater desalination, or selective ion separation, and nuclear wastewater separation to remove nuclear radioactive elements from nuclear wastewater, heavy metal removal, biorefinery, laundry water treatment, milk concentration, blood processing such as physiological separation and blood separation to replace damaged kidney filters, and / or separation of bioplatform molecules from sources such as plants, e.g. grass, or for domestic water treatment, industrial water treatment, e.g. industrial laundry effluent, food and beverage production, chemical manufacturing effluent, paper processing, wastewater from landfills, agriculture, dairy and cheese production (including salt water treatment from cheese production), milk concentration, protein recovery from crops such as potatoes.

40. 40. A membrane or method according to any one of claims 1 to 39, wherein the membrane is for water separation, e.g. desalination or oil-water separation, or for chemical separation.

41. 41. A membrane or method according to any one of the preceding claims, wherein the two-dimensional material is treated after application of the two-dimensional material to the substrate layer.

Citation Information

Patent Citations

  • Method using metal hydroxide nano fibers to prepare high-throughput PVDF porous film

    CN107008164A

  • membrane containing graphene

    JP2016522737A

  • Graphene oxide film and related methods

    JP2018502032A

  • Carbon-containing membranes for water and gas separation

    JP2018521833A

  • Membranes with tunable selectivity

    US20170296979A1